2019
DOI: 10.1007/978-3-030-31901-4_18
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Predicting Fluid Intelligence of Adolescent Brain from T1-Weighted MRIs

Abstract: Fluid intelligence (Gf) has been defined as the ability to reason and solve previously unseen problems. Links to Gf have been found in magnetic resonance imaging (MRI) sequences such as functional MRI and diffusion tensor imaging. As part of the Adolescent Brain Cognitive Development Neurocognitive Prediction Challenge 2019, we sought to predict Gf in children aged 9-10 from T1-weighted (T1W) MRIs. The data included atlas-aligned volumetric T1W images, atlas-defined segmented regions, age, and sex for 3739 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…As we mentioned in section that several studies used sMRI-based regional brain volumes as features in different machine learning methods to predict intelligence scores 4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][27][28][29][30][31] . These studies used ∼8,500 healthy subjects for model training and then predicted the residual PIQ score of more than 3,500 adolescents with a mean square error (MSE) ranging from 86 to 103 (for a range of true residual PIQ score of [−40, 30]), or a correlation of 10% (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we mentioned in section that several studies used sMRI-based regional brain volumes as features in different machine learning methods to predict intelligence scores 4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][27][28][29][30][31] . These studies used ∼8,500 healthy subjects for model training and then predicted the residual PIQ score of more than 3,500 adolescents with a mean square error (MSE) ranging from 86 to 103 (for a range of true residual PIQ score of [−40, 30]), or a correlation of 10% (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have started to use the machine especially deep learning to predict intelligence for individuals but left many open questions. In over 20 studies corresponding to a 2019 Grand Challenge, the predicted fluid intelligence had a mean square error ranging from 86 to 103 (for a range of true residual fluid intelligence score of [−40, 30]) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . The modest accuracy may suggest the need for more sophisticated deep learning algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies argued that the attentional control mechanism, the linkage between sensory discrimination and intelligence, 57 corresponds to the volumes in brain regions such as lateral fronto-parietal cortex 58 (includes BAs 6, 8, 9), dorsal anterior cingulate 58,59 (includes BA 32), and lateral posterior cerebellum. 58 As summarized in Table 3 of the supplementary materials, recent structural MRI-based predictive methods 55,[60][61][62][63][64][65][66][67][68][69][70] that used brain regional volumes found that the fronto-parietal (includes BAs 6, 8, and 9), cingulo opercular (includes BAs 22, 41, and 42), visual (includes BAs 17, 18, and 19), somatosensory (includes BAs 1, 2, 3, 5, and 7), right posterior cingulate gyrus (BAs 23, 31), left caudate nucleus, entorhinal white matter (BA 28), globus pallidus, precentral gyrus (BA 4), corpus callosum, left/right hippocampus, parahippocampal gyrus (BA 34), thalamus, precentral gyrus (BA 4), caudate nucleus, pons, and motor (includes BAs 4 and 6) cortex areas are related to the fluid intelligence in adolescents. This study predicted the residual fluid intelligence score of more than 3500 adolescents with a mean square error (MSE) ranging from 92 to 101 (for a range of true residual fluid intelligence score of [-40, 30]), 55,[60][61][62][63][64][65][66][67][68][69] or a correlation of 10% (p <0.05), 70 which further strengthens the arguments from the previous studies 58,71,72 as well as the P-FIT theory.…”
Section: Structural Mri To Infer Intelligence and Neurocognitionmentioning
confidence: 99%
“…58 As summarized in Table 3 of the supplementary materials, recent structural MRI-based predictive methods 55,[60][61][62][63][64][65][66][67][68][69][70] that used brain regional volumes found that the fronto-parietal (includes BAs 6, 8, and 9), cingulo opercular (includes BAs 22, 41, and 42), visual (includes BAs 17, 18, and 19), somatosensory (includes BAs 1, 2, 3, 5, and 7), right posterior cingulate gyrus (BAs 23, 31), left caudate nucleus, entorhinal white matter (BA 28), globus pallidus, precentral gyrus (BA 4), corpus callosum, left/right hippocampus, parahippocampal gyrus (BA 34), thalamus, precentral gyrus (BA 4), caudate nucleus, pons, and motor (includes BAs 4 and 6) cortex areas are related to the fluid intelligence in adolescents. This study predicted the residual fluid intelligence score of more than 3500 adolescents with a mean square error (MSE) ranging from 92 to 101 (for a range of true residual fluid intelligence score of [-40, 30]), 55,[60][61][62][63][64][65][66][67][68][69] or a correlation of 10% (p <0.05), 70 which further strengthens the arguments from the previous studies 58,71,72 as well as the P-FIT theory. Another study 73 involving a comparatively smaller adult data cohort (N = 211) reported a positive correlation of overall gray matter volume with fluid intelligence (r = 0.16; p < 0.01), working memory (r = 0.21; p < 0.01), and quantitative reasoning (r = 0.26; p < 0.01).…”
Section: Structural Mri To Infer Intelligence and Neurocognitionmentioning
confidence: 99%
See 1 more Smart Citation